PORTOFOLIO (SEBAGAI KONSEP DASAR PERKEMBANGAN PENILAIAN BELAJAR SISWA) - Mayang Sari Lubis (Jurnal At-Tabayyun, 2018)
In the world of education often to find out the success or the success of student learning are determined from the results (values) have been obtained. So it's not uncommon to the existence of the presumption "If value (number) high students gain and he has done a good learning process, otherwise" If the value low (number) then the students are less successful in following the instruction. Whereas in the assessment can be intangible knowledge (cognitive), skills (psychomotor) and attitude (affective). The developments here could be interpreted as a qualitative change to fruition or benefits for others, not just yourself (students). This description may already provide enough description of the nature of the assessment. Because the education agencies current emerged as a container for studied experienced delays. One of the reason is not yet fully implementing the process of learning activities can analyze or expose data about the individual differences of individuals among the educational world or society.